KARAKTERISTIK HARMONI DALAM KAJIAN QUR’ANI - Roswati Nurdin (IAIN Ambon, 2017)
Diversity on the one hand is positive, but on the other hand prone to give rise to a conflict of interest, both between groups, ethnicities, religions, and between regions. Therefore behind diversity (plurality) is needed relationship harmony. Harmony aims to achieve peace, both in domestic life, and the life of the state, to realize a harmonious and peaceful interaction. The harmony of the universe covers regularity, harmony among fellow beings, and peace among humans. The word harmony in the Qur'an is not found, but the characteristics of harmony in the sense of balance can be traced, among others, on al-musâwâ (equality) and all derivatives, al-Hurriyah (freedom) and explanation as well as al-‘adâlah (justice) and the division-division. Keywords: characteristics, harmony, qur'ani.